Cosmic-ray sum rules - Frandsen, M; Masina, I; Sannino, F (2011)
We introduce new sum rules allowing to determine universal properties of the unknown component of the cosmic rays; we show how they can be used to predict the positron fraction at energies not yet explored by current experiments, and to constrain specific models. © 2011 American Physical Society.